Robotic Process Automation (RPA) as a technological tool for automating the execution of audits - Figueroa Moreno, Jefferson Humberto (2023)
The purpose of the research was to analyze the Robotic Automation of Processes as a technological tool aimed at automating auditing processes. It is a technological alternative that uses robots called bots, which are configured in a simple way and enable a digital transformation in which they can learn and imitate tasks, which are then executed automatically. Regarding the study methodology, it was a documentary research, carried out through a review of documents, scientific articles, research, web pages, among other sources. Among the main audit activities that can be performed with the application of robotic automation of processes are identified reconciliations, queries to identify the accounts to be reconciled, trial balances, list of transactions, comparison of the lists with the consolidated reports. Similarly, analytical processes can be performed, such as starting the session with working papers of previous audits, queries to identify audited amounts; internal control processes such as population tests, purchase orders, documents and invoices, verification of prices against quantity of items, generating alerts when deviations occur. Finally, there are several advantages of this technology, such as the possibility of performing advanced data analysis, considerable reduction of audit costs, due to the reduction of human errors and therefore greater productivity, since the optimization of processes allows the staff assigned to the execution of the audit to focus their efforts on more strategic activities, such as the preparation of the final audit report.